COVID-19 Pandemic-to-Endemic Transition in Indonesia: What Does the Future Hold? - Robert Sinto (Interna Publishing, 2022)
Since first reported in December 2019, SARS-2 Coronavirus (SARS-CoV-2) infection has become a world-class pandemic, overwhelming every aspect of the global system. Globally, 526 billion confirmed cases with 6,3 billion death cases were reported by World Health Organization (WHO) by 31 May 2022. In that period, Indonesia has reported 6 billion confirmed cases with a case fatality rate reaching 2.58%. The number of new weekly cases and new weekly death have continued the declining trend observed since its peak in January 2022, i.e. 3% decrease of new weekly cases and 11% decrease of new weekly death as compared to the previous week. In response to the current epidemiology improvement, countries including Indonesia have relaxed some regulations on COVID-19 as the preparation for pandemic-to-endemic transition. Endemic is not equal to harmless. Commonly, endemic is falsely interpreted as the end of COVID-19, bringing to a false complacency. Endemic "label" on an infectious disease, such as malaria, HIV infection, tuberculosis in certain regions of the world, means the overall rates of infection are static - neither rising nor falling. Endemic "label" defines nothing about time duration to reach disease end or how many populations will still be susceptible to the disease. Therefore, transition for pandemic-to-endemic of COVID-19 could not simply translated into the end of either public and health service awareness, or research on COVID-19. It then should add new emerging perspective on COVID-19 research as was mandated by WHO. One example of which is evidence-based strategies for infection prevention control and personal protective equipment for infection control de-escalation in relation to COVID-19 pandemic scaling back. In the spirit of nurturing research and publication in this transition for pandemic-to-endemic era, the Indonesian Journal of Internal Medicine published various COVID-19 associated-original articles, systematic review, and case series across various COVID-19 condition. Atici, et. al. and Tunjungputri, et. al. report articles on factors and treatment that is associated with higher COVID-19 survival. Corticosteroids, Interleukin-6 inhibitors and anticoagulant administered to the proper subset of COVID-19 population are several beneficial treatments among limited evidence-based proven treatment available today. These supportive treatments, whenever indicated at the proper time, should be considered in managing every COVID-19 patient. In addition, high antibiotic use in COVID-19 patients despite low secondary bacterial infection has been widely reported. Chen, et. al. report a similar situation in Indonesia and should raise the awareness of antimicrobial resistance thread now and in the future. Together with proper diagnostic stewardship, the simple predictors of secondary bacterial infection that have been concluded could potentially be used to reduce liberal antibiotic use while optimizing the use in indicated patients. Prabowo, et al. enriched our understanding on usage of telemedicine to monitor post COVID-19 condition in Indonesian populations. High quality research has, and will again, save the livelihoods of people across the world. While future pandemics could not be completely prevented, the research infrastructures that have built during last 2 years could be used as a strong modality to be better prepared and coordinated in future outbreak/ pandemic response by detecting and preventing the emerging diseases at their very early stage. Waste in COVID-19 research and multiple COVID-19 associated research article retractions should caution researchers -as evidence-producer- and clinicians -as evidence-user- in prioritizing the scientific inquiry and questioning individual conflict of interest. Insightful articles addressing the multitude aspects of the COVID-19 pandemic-to-endemic transition related topics are still needed in the future.